Perancangan Interior Playhouse Daycare di Surabaya - Yenni Beatrix Tejo; Andereas Pandu Setiawan; Jean Francois Poillot (Intra, 2019)
The busy activities of working parents makes it difficult for them to take care of their children. With the presence of educative daycare parents are expected to be able to entrust their children without worry when they are working. The methods used in the design process are understanding, observe, point of view, ideate, prototype, test, storytelling, and business model.This design is divided into 4 areas, namely, entertainment area, study area, rest area, and service area. The concept used in this design are fun and satisfying in space. The entertainment area is the center of children's activities so a spacious entertainment area is provided. The material used are mostly wood, while the colors used are pastel colors.